(untitled) (Research, Society and Development, 2023)
Introduction: At the end of 2019 in the province of Wuhan, China, a new virus was discovered, SARS-CoV-2, which is the main cause of various types of pneumonia (Cardoso et al, 2020). Since the beginning of the pandemic, there has been concern about the virus infection in pregnant women (Cardoso et al, 2020). What are the transmission routes, so this study is of great relevance to the scientific community in the health area from the location chosen for the study. Objective: To analyze the maternal, fetal and neonatal outcomes of parturients diagnosed with Covid-19 treated at a maternity hospital in the Northwest of the state of Rio Grande do Sul. Method: A documentary research of a quantitative nature was developed. The study was developed through the analysis of electronic medical records from the maternity sector of Hospital Santo Antônio in the municipality of Tenente Portela. The sample consisted of 10 medical records, with the records being analyzed from January 2020 onwards. For data analysis, the Statistical Package for Social Science (SPSS) version 21.0 program was used. Results: Of the 10 deliveries, prematurity occurred in three cases. Regarding the beginning of labor, 9 was spontaneous and none required hospitalization in the intensive care unit. Conclusion: With the development of this study, it was possible to identify that most pregnant women contract Covid-19 in the third trimester of pregnancy, in line with data present in other studies.